Potential Identification and Business Development Strategies for Freshwater Fish Cultivation in Ogan Komering Ulu District - Betaria Dwisepti; Munajat Munajat; Rini Efrianti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Freshwater aquaculture is one of the businesses that have promising prospects. From an economic point of view, this business provides promising benefits. With good processing, freshwater fishery commodities become superior. This research aimed to identify and analyze the potential for developing freshwater aquaculture in Ogan Komering Ulu District and finding strategies to establish the potential for developing freshwater aquaculture businesses in Ogan Komering Ulu District. The method in this study used the survey method. The data collection method is an exploratory qualitative data collection method. The data analysis technique used is allocation Quotient (LQ) analysis, Shift-Share analysis, and SWOT analysis. The results of the study found that the freshwater aquaculture business in Ogan Komering Ulu District can be developed using strengths using existing opportunities and this is a very good situation where Ogan Komering Ulu District has freshwater aquaculture business by taking advantage of existing opportunities. The strategy that can be used is the SO Strategy, namely (Strength and Opportunities), which is a strategy that optimizes strengths to take advantage of opportunities (opportunities), namely optimizing land by utilizing the Ogan river as cages/fish ponds, increasing the role of the government in supporting the marketing of products. freshwater fish production at OKU and increased production to meet market demand.